Azucena A. Fraboschi y otros (eds.), Cartas de Hildegarda de Bingen. Volumen I, Buenos Aires, Mino y Davila Editores, 2015, 303 pp. - Ortíz, María Esther (2017)
Fil: Ortíz, María Esther. Pontificia Universidad Católica Argentina; Argentina